Effect of aromatherapy on sleep quality of ICU patients with myocardial infarction (芳香疗法改善ICU心肌梗死患者睡眠质量的效果) - LIN Zhongbao (林忠宝); CHEN Dandan (陈丹丹); YE Mei (叶梅); SHI Lan (石岚) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of aromatherapy with Lavender essential oil on improving sleep quality of patients with myocardial infarction in ICU. Methods Thirty patients with myocardial infarction admitted to ICU from June 2019 to March 2020 were selected as the control group, and 31 patients with myocardial infarction admitted to ICU from April 2020 to January 2021 were selected as the intervention group. After admission, patients in both groups were surveyed by Richards-Campbell Sleep Questionnaire (RCSQ). The control group received routine nursing measures, and smart bracelet was used to monitor the patient sleep quality. The intervention group was given extra aromatherapy by using Lavender essential oil. Monitoring data was collected daily, and a survey with RCSQ was conducted 5 days after intervention. Results The total RCSQ score of the intervention group was (64. 13±4. 92) points, which was higher than that of the control group (49. 40±4. 32) points, with a significant difference (P<0. 05). The total sleep time of the intervention group was (6. 93±0. 37) h, which was higher than that of the control group (4. 81±0. 32) h, with a significant difference (P<0. 05). Conclusion Aromatherapy with lavender essential oil can effectively improve the sleep quality of ICU patients with myocardial infarction. (目的 观察薰衣草精油芳香疗法在改善ICU心肌梗死患者睡眠质量中的效果。方法 选取2019年6月-2020年3月ICU收治的心肌梗死患者30 例为对照组, 2020年4月-2021年1月ICU收治的心肌梗死患者31例为干预组。入科后2组患者均行Richards-Campbell睡眠量表 (RCSQ)问卷调查。对照组患者给予常规护理, 入睡前佩戴具有睡眠监测功能的手环, 干预组除接受常规护理及睡前佩戴同型号手环外, 使用薰衣草精油滴于患者枕头行芳香疗法干预。每日记录手环上睡眠情况收集客观指标, 5 d后再次行RCSQ问卷调查。结果 干预组RCSQ总分为(64. 13±4. 92)分, 高于对照组的(49. 40±4. 32)分, 差异有统计学意义(P＜0. 05)。干预组总睡眠时间(6. 93±0. 37) h, 高于对照组(4. 81±0. 32)h, 组间差异有统计学意义(P＜0. 05)。结论 薰衣草精油芳香疗法可以有效改善ICU心肌梗死患者睡眠质量。)